Corpo próprio e cogito tácito em Merleau-Ponty - Azevedo, Denis de Souza (2015)
The Merleau-Ponty phenomenology’s, with the desire not to put the subject or the world as precedence to understand the relationship of being and living world, splits with the main philosophical currents of modernity, namely: intellectualism and empiricism. To overcome this, Merleau-Ponty resorts to notion of body lived and presents an approach about the perception always from the point of view of the perceiver. Thus, the being-in-the-world, located in their surrounding world, is constantly in relationship with this without distinguishable ever. The cogito, therefore, elevated to absolute by Descartes, reverts to “worldly” in this phenomenological philosophy, given that the thought no longer has the power to all “swallow” separate from the world. Being-in-the-world, in short, is to be in an experiential effectiveness, in which subject and world intertwined in a mutuality that form the unique experience possible. Finally, our work will focus on overcoming this phenomenology front of the egoic absolutism left by the intellectualism of Descartes.